Analisis pelaksanaan pembelajaran matematika kelas iv di mi nu hidayatul mubtadiin - Nurullaika, Nurullaika; Rahmah, Nabila (Maliki Interdisciplinary Journal, 2025)
This research aims toknow in depth about the implementation of mathematics learning in class IV MI NU Hidayatul Mubtadi’in. Research This study describes the process of implementing mathematics learning in grade 4 MI NU Hidayatul Mubtadiin. The method used The method used in this research is a qualitative descriptive method, a method that focuses on the method that focuses on problems based on facts that are carried out directly, a research approach used to describe and understand the process of implementing mathematics learning in class 4 directly, a research approach used to describe and understand naturally occurring phenomena. phenomena that occur naturally. The results of this study reveal that the process of implementing learning in class IV has gone well and is in accordance with the general steps of learning. in accordance with the general steps of learning. The results of The results of this study can be used as data and reference for teachers and schools in the learning implementation process. school in the process of implementing learning. Researchers hope that this research can be an evaluation for teachers in the process of implementing learning in the future.